2020
DOI: 10.1017/ice.2020.1304
|View full text |Cite
|
Sign up to set email alerts
|

A survey of preparedness against coronavirus disease 2019 (COVID-19) in hospitals in Tokyo, Japan, with healthcare personnel with COVID-19 and in-facility transmission

Abstract: A questionnaire was distributed to hospitals in Tokyo (N=38) asking about their preparedness against, and in-facility transmission of, COVID-19. As of May 31, 2020, 284 HCP contracted COVID-19, and in-facility COVID-19 transmission occurred at 13 hospitals, negatively impacting hospital functions and patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Cases of COVID-19 related to nosocomial transmission involved 66 inpatients (15%) in London in March and April 2020 and patients at several hospitals in Tokyo (Japan) in May 2020 [ 41 , 42 ]. In hospital-acquired cases, the possible routes of infection are direct contact with patients residing in the same bay and indirect contact via facility sharing or staff movement, and a high rate of mortality has been observed [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cases of COVID-19 related to nosocomial transmission involved 66 inpatients (15%) in London in March and April 2020 and patients at several hospitals in Tokyo (Japan) in May 2020 [ 41 , 42 ]. In hospital-acquired cases, the possible routes of infection are direct contact with patients residing in the same bay and indirect contact via facility sharing or staff movement, and a high rate of mortality has been observed [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“… 42 Tagashira, Takamatsu, Hasegawa, Uenoyama and Honda in their study on preparedness against COVID-19 in Japan, reported that hospital preparedness in the early phase of the pandemic was linked with nosocomial transmission in healthcare personnel. 43 …”
Section: Discussionmentioning
confidence: 99%
“…42 Tagashira, Takamatsu, Hasegawa, Uenoyama and Honda in their study on preparedness against COVID-19 in Japan, reported that hospital preparedness in the early phase of the pandemic was linked with nosocomial transmission in healthcare personnel. 43 With respect to personal preparedness, almost 90% of the sample did not feel professionally prepared for this pandemic. Additionally, more than 80% of the respondents considered inadequate the training concerning COVID-19 and the use of PPE.…”
Section: Discussionmentioning
confidence: 99%
“…The sudden increase in COVID-19 cases is imparting high pressure on healthcare services worldwide [ 92 , 93 ]. Precise diagnosis of COVID-19 infected patients is fundamental in the process of providing proper treatment and avoiding the overburdening of the healthcare system.…”
Section: Role Of Ai In the Screening Of Covid-19 Infected Patients And Diagnosismentioning
confidence: 99%